Analysis of the attitude of high school students to innovative types of motor activity in the system of school physical education - Tetiana Bala; Anhelina Petrova (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to study the subjective attitude of high school students to innovative types of motor activity in physical education lessons according to the questionnaire. Material & Methods: theoretical analysis and synthesis of scientific and methodological literature, a survey and methods of mathematical statistics. The study involved 112 students in grades 10-11. Results: it was revealed that the vast majority of schoolchildren are positive about the introduction of CrossFit into the system of school physical education, since students are dissatisfied with the content of existing physical education lessons, the main reason they note the uniformity of the educational material. Conclusion: established a positive attitude of senior students of institutions of general secondary education on the introduction of CrossFit as an innovative means of physical education.